The Crisis of Adults and Its Implications for the Youth. A Theological-Pastoral Study within the Context of Croatia and the Roman Catholic Church Teaching - Razum, Ružica (Verbum Vitae, 2024)
This article aims to show the connection between the current crisis of adults and the changes that can be observed in the level of religiosity/spirituality of today’s youth. The Roman Catholic Synod on Young People held in Rome highlighted the need to understand young people and their religiosity. Understanding and interpreting the religiosity, ecclesiasticism, and spirituality of today’s youth is necessary if we wish to answer their religious and spiritual questions properly. Nonetheless, this paper considers only one specific aspect of youth religiosity, that is, the connection between the world of adults, especially the crisis that has affected many of them, and the development of young people—especially of their spirituality/religiosity. The first part provides a basic outline of young people’s religiosity and their relationship to the Roman Catholic Church based on the research. The second part reflects on the crisis of intergenerational transmission of faith, critically evaluating the existing channels used for this purpose. The third part is a critical evaluation of some aspects of the life of adults, especially in light of the crisis that has affected adulthood. The last part, containing results and conclusion, emphasizes the necessity and importance of the formation of adults in the Roman Catholic Church. The research is based on a literature review, analysis of data obtained from research—carried out especially in the Republic of Croatia—as well as directions that come to us from the Roman Catholic Church documents.